Living Through the Life-Altering Loss of a Child: A Narrative Review. (3rd July 2015) - Price, Jayne E.; Jones, Anne Marie
Abstract : The death of a child is a life-altering event for parents, leading to grief that is individual, intense, and long lasting. The grief experienced by parents following the death of their child can affect their relationships and as they sometimes see it, their role within society. Parents can find grief isolating, due to society's lack of understanding of their grief experience. Gendered differences in grief reactions have also been noted. Theoretical understandings of bereavement, now acknowledge parental need "not to let go" but rather to reconstruct relationships with their deceased child in terms of a continuing bond. This narrative literature review draws together theory and research on the topic, highlighting current knowledge and suggesting ways in which children's nurses can support parents as they live through the loss of their child.